162k views
15 votes
How would you solve this


How would you solve this ​-example-1
User TehSphinX
by
5.8k points

1 Answer

6 votes


\qquad\qquad\huge\underline{{\sf Answer}}♨

Let's write the equation in standard form ~


\qquad \sf  \dashrightarrow \: {x}^(2) + {y}^(2) - 2y - 15 = 0


\qquad \sf  \dashrightarrow \:(x ){ }^(2) + {y}^(2) - 2y = 15


\qquad \sf  \dashrightarrow \:(x ){ }^(2) + {y}^(2) - 2y + 1 = 15 + 1


\qquad \sf  \dashrightarrow \:(x ){ }^(2) +( {y}^{} - 1 ) {}^(2) = 16

Now, it's the required form of circle ~

User MrVoodoo
by
5.5k points